Preference for Rasm Al-Qur’ān among Tahfiẓ Students: A Study of Living Qur’ān at the Ma’had Amaliyyah Qurani Islamic Boarding School in Bandung Regency - Mochammad Ikhsan; Muhammad Ruhiyat Haririe (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2026)
This study discusses the tahfiẓ students’ preferences for two models of rasm Al-Qur’an: rasm ‘Utsmāni and rasm Imlā’i, in the context of the practice of reading the Qur’an in Islamic boarding schools. This study departs from the shift in the discourse of rasm from the normative-theoretical realm to practical issues regarding the usability of the mushaf for its readers. The study was carried out using a living Qur’an approach with qualitative field methods in the Ma’had Amaliyyah Qurani Islamic Boarding School, Bandung Regency. Data were collected through reading observations and semi-structured interviews with 20 tahfiẓ students using QS. al-Fatḥ /48:29 in two mushafs: the 2019 Revised Edition of the Indonesian Standardized Mushaf as a representation of rasm ‘Utsmāni and the 1974 edition of the Pojok Menara Kudus Mushaf as a representation of rasm Imlā’i. The results showed that all respondents preferred MSI because they perceived it as easier and more comfortable to read. This preference was related to familiarity with using the mushaf, visual comfort, and pedagogical needs in the deposit and murāja’ah activities. These findings indicate that the issue of rasm is not only related to orthographic rules, but also to the social practice of Qur’an recitation within the tahfiẓ community